2020
DOI: 10.3389/fmicb.2019.03059
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake and Release of Amino Acids by Staphylococcus aureus at Mid-Exponential and Stationary Phases and Their Corresponding Responses to Changes in Temperature, pH and Osmolality

Abstract: Staphylococcus aureus is an important pathogen that is associated with nosocomial infections, as well as food poisoning. This bacterium is resistant to antimicrobial agents and can survive in a wide range of environmental conditions. The aim of this study was to measure the uptake and release of amino acids by S. aureus at midexponential and stationary phases of growth following exposure to a combination of conditions including variations in temperature, pH and NaCl. Bacterial cells were grown up to mid-expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…For example, while antibiotic compounds targeting the lysC riboswitch regulating lysine biosynthesis were discovered [ 105 ], the riboswitch is not considered a viable target because many bacteria harbour isozymes that are not regulated by the riboswitch [ 106 ]. Further, many pathogens can sequester lysine from the host, rendering inhibition of lysine biosynthesis ineffective [ 107 , 108 ]. Lafontaine and colleagues demonstrated that their most promising guanine riboswitch ligand PC1 ( Figure 5 b) only acts against clinically relevant bacteria that have guaA under riboswitch regulation [ 101 ].…”
Section: General Considerations For Riboswitch Drug Discoverymentioning
confidence: 99%
“…For example, while antibiotic compounds targeting the lysC riboswitch regulating lysine biosynthesis were discovered [ 105 ], the riboswitch is not considered a viable target because many bacteria harbour isozymes that are not regulated by the riboswitch [ 106 ]. Further, many pathogens can sequester lysine from the host, rendering inhibition of lysine biosynthesis ineffective [ 107 , 108 ]. Lafontaine and colleagues demonstrated that their most promising guanine riboswitch ligand PC1 ( Figure 5 b) only acts against clinically relevant bacteria that have guaA under riboswitch regulation [ 101 ].…”
Section: General Considerations For Riboswitch Drug Discoverymentioning
confidence: 99%
“…Earlier studies have shown that S. aureus altered many genes in order to combat changes in pH and hence facilitate survival [25][26][27][28] . An identical study showed that amino acid and protein composition of S. aureus were remarkably altered following exposure to either pH6 or pH8 combined with lower temperature of 35°C 6,29 . Another study determined significant changes in the fatty acid composition and cell sizes of Staphylococcus lugdunensis in response to alterations in environmental conditions including changes in pH and temperature 8 .…”
Section: Discussionmentioning
confidence: 95%
“…A recent study exhibited that hydrogen peroxide combined with other environmental factors such as altered pH and temperature led to very different metabolic profiles of a clinical isolate of S. aureus 10 , suggested these alterations in amino acids were essential for survival under changes in the environmental conditions. Moreover, a new study revealed that S. aureus taken up and released different levels of amino acids following growth in altered environmental conditions 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated how S. aureus and Staphylococcus lugdunensis adapt to changes in the environmental conditions, mimicking wound site conditions: pH 6–8, temperature 35–39 °C, and adding NaCl to increase osmolality by up to 5%. Staphylococcal species adapted to these conditions by inducing considerable alterations in the composition of membrane fatty acids and cytoplasmic amino acids, as well as changes in ribosomal proteins and cell sizes [ 6 , 19 , 20 ]. The adaptive changes also demonstrated in S. aureus under a similar design were consistent with the formation of metabolic phenotypes characteristic of the prevailing environmental conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%